Serotonin Syndrome in the Setting of Lamotrigine, Aripiprazole, and Cocaine Use. (2nd August 2015) - Kotwal, Anupam; Cutrona, Sarah L.
Abstract : Serotonin syndrome is a potentially life-threatening condition associated with increased serotonergic activity in the central nervous system. It is classically associated with the simultaneous administration of two serotonergic agents, but it can occur after initiation of a single serotonergic drug or increasing the dose of a serotonergic drug in individuals who are particularly sensitive to serotonin. We describe a case of serotonin syndrome that occurred after ingestion of higher than prescribed doses of lamotrigine and aripiprazole, in addition to cocaine abuse. The diagnosis was established based on Hunter toxicity criteria and severity was classified as mild. The features of this syndrome resolved shortly after discontinuation of the offending agents. Serotonin syndrome is characterized by mental status changes, autonomic hyperactivity, and neuromuscular abnormalities along a spectrum ranging from mild to severe. Serotonin syndrome in our patient was most likely caused by the pharmacokinetic and pharmacodynamic interactions between lamotrigine, aripiprazole, and cocaine leading to increased CNS serotonergic activity.